Phytochemical Study of Achyranthes aspera Linn - Singh Chauhan, Anurag; Rawat, G.S.; Singh, C.P. (Asian Journal of Chemistry, 2010)
Total sugar, vitamins, amino acids, nitrogen and protein were estimated from Achyranthes aspera Linn and new cyclic chain aliphatic fatty acid isolated from seeds of this plant.